Information 2.0 new models of information production, distribution and consumption - De Saulles, Martin (London Facet, 2012)
"Covering every aspect of the new digital information environment from iPads and e-books to the future of information and how it will be controlled, this landmark textbook provides a comprehensive and cutting-edge guide to what's happening, why and how information professionals can have a pivotal role in this new landscape. Drawing on international case studies and current trends it explores the fundamental changes in the four core areas of information production, storage, distribution and consumption, grappling with cutting-edge issues such as: key information trends in the last 15 years such as mass broadband; the rise of grass roots information production in social media, open access publishing and the storage of information in the cloud; how informal, digital methods of information distribution like RSS and webcasting are threatening traditional stakeholders like libraries, publishers and newspapers; the reconfiguration of the relationships between software, hardware and content creation companies; and, the need for a new information literacy and the pivotal role of the information professional." -- Publisher's description.
1. Introduction: -- What is information? -- The foundations of the information society -- The internet as a driver of change -- The big challenges of big data -- What about the information providers? -- New ways of creating information -- Where do we put all this information? What information matters -- 2. New models of information production: -- Introduction -- Blogs and the challenge to publishers -- Wikis and collaborative publishing -- Search engines and what they know -- Podcasting and the democratization of the media -- The challenge of big data -- Concluding comments -- Questions to think about -- 3. New models of information storage: -- Introduction -- Preserving the internet -- How organizations store information -- Legal requirements -- Data mining -- Collection digitization -- Keeping it all safe -- Storage at the personal level -- Putting it in the cloud -- Our digital footprints -- The future of storage -- Concluding comments -- Questions to think about -- 4. New models of information distribution: -- Introduction -- The architecture of the internet -- Distribution and disintermediation -- The new intermediaries -- Online video- we're all celebrities now -- Open government and the internet -- Threats to the open web -- Concluding comments -- Questions to think about -- 5. New models of information consumption: -- Introduction -- Information consumption devices -- Looking beyond the artefact -- Information ecosystems: glided cages or innovation hotbeds? -- Returning to an open web -- Rent or buy? -- Making sense of it all -- Implications for information professionals -- Concluding comments -- Questions to think about -- 6. Conclusion: -- Introduction -- Implications for information professionals -- Implications for publishers -- Implications for society -- Concluding comments.
Includes bibliographical references (p. [125]-133) and index.
Keywords: Information services; Social media; Information retrieval -- Technological innovations